1977
DOI: 10.1002/j.2050-0416.1977.tb03823.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Levels in Air-Saturated Worts

Abstract: The dissolved oxygen contents of air-saturated worts and sucrose solutions determined with an internally calibrated polarographic oxygen electrode show a linear decrease in the gravity range 1 -016-1 -075. The level at S.G. 1 040 is 8 5 mg/litre at 20 C.Key words: oxygen, wort, analysis-method. IntroductionThe measurement of the absolute quantity of dissolved oxygen in wort is difficult because of the interference of organic materials in chemical methods*-7 and the problem of relating the activity or partial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As higher-gravity worts have reduced oxygen solubility compared with standard gravity worts (70), under-oxygenation can lead to suboptimal revitalization of the yeast, growth defects and low subsequent fermentation rates (71). Moonjai et al (72) demonstrated the potential of UFA lipid supplements to wort as an alternative to wort oxygenation (without losing fermentation potency or organoleptic quality).…”
Section: High-gravity Brewing As a General Influence On Beer Flavourmentioning
confidence: 99%
See 1 more Smart Citation
“…As higher-gravity worts have reduced oxygen solubility compared with standard gravity worts (70), under-oxygenation can lead to suboptimal revitalization of the yeast, growth defects and low subsequent fermentation rates (71). Moonjai et al (72) demonstrated the potential of UFA lipid supplements to wort as an alternative to wort oxygenation (without losing fermentation potency or organoleptic quality).…”
Section: High-gravity Brewing As a General Influence On Beer Flavourmentioning
confidence: 99%
“…As higher‐gravity worts have reduced oxygen solubility compared with standard gravity worts , under‐oxygenation can lead to suboptimal revitalization of the yeast, growth defects and low subsequent fermentation rates . Moonjai et al .…”
Section: Introductionmentioning
confidence: 99%
“…Wort lipid modification through, for example, trub addition may have application in decreasing the disproportionate production of esters. Ester synthesis is known to be reduced by excess oxygen 7 and solubility of oxygen is reduced at higher gravities 14 . These facts may, in part, explain the higher production of esters during high gravity brewing.…”
Section: Wort Turbidity and Fermentationmentioning
confidence: 99%
“…The potential for UFA-supplementation to replace wort oxygenation at an industrial scale has been shown by Hull et al 90 In this case, exposure of pitching yeast to olive oil (a source of oleic acid) prior to fermentation was used rather than wort aeration, without major effects on the acceptability of the beer produced. UFA supplementation therefore acts as a form of oxygen credit and may be of particular benefit in the case of HG and VHG gravity worts in which solubility of oxygen may be limited 14 . High gravity worts typically require a higher rate of oxygenation to ensure that the fermentation proceeds adequately, though how much of this oxygen is available for yeast metabolism and how much is lost from the wort is open to question 27 .…”
Section: Fatty Acid Supplementsmentioning
confidence: 99%
See 1 more Smart Citation